Development of a simple, rapid and specific RP-HPLC method for the estimation of pyridoxine hydrochloride and doxylamine succinate in bulk and combined pharmaceutical dosage forms - AMAR KUMAR KASTURI; KANAKA RAJU MEDICHERLA; N. BALAKRISHNAN (International Journal of Pharma and Bio Sciences, 2018)
A rapid and specific method was developed and validated for the quantitation of Pyridoxine Hydrochloride and Doxylamine in bulk and combined pharmaceutical dosage forms. To acheive the chromatographic separation Shimadzu system has been used, equipped with LC-20AD high-performance liquid chromatography, degasser PGU-20A 5, variable wavelength programmable diode array detector SPD-M20A, auto sampler SIL-20 AC HT, and column oven CTO-10 A5 VP hic separation was achieved by using Shimzadu prominence LC-20AD high-performance liquid chromatography, equipped with degasser PGU-20A 5, variable wavelength programmable diode array detector SPD-M20A, auto sampler SIL-20 AC HT, and column oven CTO-10 A5 VP. XBridge C18, 4.6 mm X150 mm, 5 microns Make: Waters, Water’s Corporation. Inc. The proposed method was validated for selectivity, precision, linearity and accuracy. The developed method was successfully applied to estimate the amount of Pyridoxine Hydrochloride and Doxylamine in bulk and combined dosage forms.